Characterisation of a group of endogenous gammaretroviruses in the canine genome - Tarlinton, Rachael E.; Barfoot, Hannah K.R.; Allen, Ceri E.; Brown, Katherine; Gifford, Robert J.; Emes, Richard D. (Elsevier, 2013)
Bioinformatics were used to identify and characterise 39 pol, 34 gag and five env gammaretroviruses within the canine (Canis lupus familiaris) reference genome. These endogenous retroviruses are monophyletic to the Canidae, predate the divergence of dogs and foxes and are fixed in 20 canine breeds examined. They are transcribed in normal canine tissue but are unlikely to be replication competent in dogs.